1997
DOI: 10.1590/s0102-76381997000300004
|View full text |Cite
|
Sign up to set email alerts
|

Cirurgia de revascularização do miocárdio minimamente invasiva: resultados com o uso da videotoracoscopia e do estabilizador de sutura

Abstract: Objetivo: No sentido de associar os maiores benefícios da operação de revascularização do miocárdio tradicional com a utilização da anastomose da artéria interventricular anterior, com vários dos benefícios da angioplastia, alguns grupos têm começado a realizar a cirurgia de revascularização do miocárdio minimamente invasiva. O objetivo deste trabalho é o relato de nossa experiência inicial com essa abordagem técnica, especialmente com a utilização de videotoracoscopia (VDT) e do estabilizador de sutura (ES). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 0 publications
0
8
0
2
Order By: Relevance
“…Brazil has been included in this list through the experiments carried out by Jatene et al [17], who in 1997 reported the use of videothoracoscopy to dissect the left internal thoracic artery (LITA) and its coronary implant through minithoracotomy. Seventy-three patients were operated on with a low index of complications and early hospital discharge.…”
Section: Resultsmentioning
confidence: 99%
“…Brazil has been included in this list through the experiments carried out by Jatene et al [17], who in 1997 reported the use of videothoracoscopy to dissect the left internal thoracic artery (LITA) and its coronary implant through minithoracotomy. Seventy-three patients were operated on with a low index of complications and early hospital discharge.…”
Section: Resultsmentioning
confidence: 99%
“…Brazil is included in this transition with the experiences of Jatene et al [3], who, in 1997, reported the use of videothoracoscopy for dissection of the left internal thoracic artery and its coronary implantation through minithoracotomy. Seventy-three patients underwent surgery with a low rate of complications and with early hospital discharge.…”
Section: Discussionmentioning
confidence: 99%
“…These studies show that such a technique is recommended as the first option for valve procedures [2][3][4][5][6]. The robot improves this new technique by providing dexterous instruments that answer to voice commands or can be controlled by a joystick.…”
Section: Discussionmentioning
confidence: 99%
“…A experiência de JATENE et al (26) publicada recentemente, usando estabilizador de sutura, evidenciou excelentes resultados, proporcionando maior facilidade, segurança e qualidade na confecção das anastomoses.…”
Section: Comentáriosunclassified